Analisis Kesalahan Berbahasa Pada Koran Sumatera Ekspres Edisi Minggu, 6 November 2023 - Eva Mispita; Puspa Indah Utami; Dessy Wardiah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Language error is the use of language both orally and in writing that deviates from the rules of Indonesian grammar. The problem discussed in this study is the analysis of language errors in the Sunday, November 6, 2023 edition of the Sumatra Ekspres newspaper. This study aims to describe language errors in Sumatra Express newspaper. The method used in this study is qualitative descriptive method. The object of research used is the Sumatra Express newspaper with observation, listen, and record research techniques. The results of this study stated that there were still some language errors found in the Sumatra Express newspaper, errors contained in the newspaper, namely, errors in the use of punctuation. In the Sumatra Express newspaper, punctuation errors lie in title names that are not punctuated with periods (.) or commas (,). Spelling errors, misuse of standard words, and word choice errors are still found in Sumatra Express newspapers. But for the misuse of capital letters is not found in the Sumatra Express newspaper.